Value for Money in Organizations Providing Public Education Services and How to Measure It - Štrangfeldová, Jana; Štefanišinová, Nikola (Naše gospodarstvo/Our economy, 2020)
The public has put increased pressure on organizations providing public services to demonstrate the most productive use of resources, with due regard for value received. Education is no exception. This study focus on the presentation and evaluation of public organizations (public grammar schools in our case) in education on the basis of their economy, efficiency and effectiveness as one of the indicators of performance assessment. The methodology of Value For Money presented in this study can provide useful information about the situation of education for public forces and for public grammar schools themselves. Also, this methodology may help to gain a deeper insight into strengths of individual schools, as well as in which they can improve. A limitation of the concept of VFM is that performance evaluation is possible only between homogeneous services. The originality and value of the study are reflected in its focus on such topics as monitoring and measuring of performance for public service organizations (i.e., education services ). It also provides a tool for districts and individual schools to gain information using indicators employed here for identifying and solving the performance problems that occur in education system of Slovakia.
Keywords: performance; value for money; economy, efficiency; effectiveness; organizations providing public services; education